Target cum flexibility: synthesis of C(3 `)-spiroannulated nucleosides - Dushing, Mangesh P.; Ramana, C. V. (Tetrahedron Letters, 2011)
We report a simple strategy for the synthesis of a collection of C(3')-spirodihydroisobenzo-furannulated nucleosides featuring a [2+2+2]-cyclotrimerization as the key reaction. The cyclotrimerization reactions are facile with the unprotected nucleosides having a diyne unit. When both alkynes of the diyne are terminal, the regioselectivity is poor. However, when one of the terminal alkynes is additionally substituted, the cyclotrimerizations are highly diastereoselective. Since the key bicycloannulation is the final step, this strategy provides flexibility in terms of the alkynes and is thus amenable for the synthesis of a focussed small molecule library. (C) 2011 Published by Elsevier Ltd.
Keywords: Dihydroisobenzofuran; Modified nucleosides; Tanaka catalyst; Willkinson catalyst; [2+2+2]-Cyclotrimerization